2017
DOI: 10.1002/anie.201711031
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐ and Bis(imidazolidinium ethynyl) Cations and Reduction of the Latter To Give an Extended Bis‐1,4‐([3]Cumulene)‐p‐carboquinoid System

Abstract: An extended π-system containing two [3]cumulene fragments separated by a p-carboquinoid and stabilized by two capping N-heterocyclic carbenes (NHCs) has been prepared. Mono- and bis(imidazolidinium ethynyl) cations have also been synthesized from the reaction of an NHC with phenylethynyl bromide or 1,4-bis(bromoethynyl)benzene. Cyclic voltammetry coupled with synthetic and structural studies showed that the dication is readily reduced to a neutral, singlet bis-1,4-([3]cumulene)-p-carboquinoid as a result of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…7 a Similar observations have been also made in many other closed-shell compounds reported recently. 11a , 14 , 23 Baumgarten 6 c addressed this issue in a very recent report that concludes that the weak intensity triplet expected for CH can be masked under even ≈0.1% of mono-radical impurity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 a Similar observations have been also made in many other closed-shell compounds reported recently. 11a , 14 , 23 Baumgarten 6 c addressed this issue in a very recent report that concludes that the weak intensity triplet expected for CH can be masked under even ≈0.1% of mono-radical impurity.…”
Section: Resultsmentioning
confidence: 99%
“… 12 Remarkably, during the preparation of this manuscript for submission, we came across three consecutive reports dealing with the synthesis of extended cumulenes IV supported by CAACs 13 or a classical N-heterocyclic carbene (NHC). 14 Very recently, we reported stable crystalline radicals V derived from classical NHCs. 15 While these reports nicely emphasize the relevance of singlet carbenes in the synthesis of carbon-centered π-conjugated systems and radicals, synthetic access to diradicaloids VI , which are NHC-analogues of I , remained a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…There are plenty of [3]cumulenes that have been synthesized, but just a small fraction of them have been reported with a C‐C‐C angle of less than 170°, with 165° being the smallest up to now . This absence of perfect linearity can be attributed to steric repulsions in the crystal, but some theoretical calculations have shown that this slightly bent structure persists or that the bending potential is very shallow in the gas phase . This shallow potential energy surface could be attributed to other resonant structures, like the ones responsible for the bent structures of the heavier E 2 L 2 compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Further examples of cumulenes connected by two NHCs with saturated 39 , 40 and unsaturated 41 backbones were very recently reported. Equally, heterocyclic carbenes can stabilize cumulenes and carbon allotropes, 42 , 43 which show unique optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%